Bio‐inspired nano rotor investigation based on UVLM. Issue 1 (4th February 2020) - Shanyong, Zhao; Zhen, Liu; Yachuan, Sun; Tianjiao, Dang; Shiqi, Li
Abstract : Nano rotor is of great value in military and civilian applications. Due to its nano size, it works at an ultra‐low Reynolds number and aerodynamic performance deteriorates dramatically. The bio‐inspired nano rotor is carried out to improve the rotor propulsive performance. Unsteady vortex lattice method (UVLM) model is established fully considering the influence of induced drag and wake vortex distortion on aerodynamic forces. The aim is to quickly and accurately simulate the flow field around the bio‐inspired nano rotor and to efficiently perform the aerodynamic calculation to optimise the design of the bio‐inspired rotor. The rotor parameters and motion parameters such as aspect ratio, taper ratio and camber are studied using UVLM. It is found that the aerodynamic performance of the rotor increased with the aspect ratio. The quality factor changes parabolically with the taper ratio and camber, and there is an optimal value for the ratio and camber, respectively. The influences of pitching angle and frequency are investigated as well. Results show that the bio‐inspired motion improves the propulsion performance of nano rotor.